Improving fiscal transparency to raise government efficiency and reduce corruption vulnerabilities in Central, Eastern, and Southern Europe - Akitoby, Bernardin (Washington, D.C International Monetary Fund (IMF), 2020)
This departmental paper investigates how countries in Central, Eastern, and Southeastern Europe (CESEE) can improve fiscal transparency, thereby raising government efficiency and reducing corruption vulnerabilities. (IMF page)
Acknowledgments -- Executive Summary -- 1. Introduction -- 2. Fiscal Transparency, Government Efficiency, and Corruption Vulnerabilities -- 3. Assessing Fiscal Transparency in CESEE -- 4. The IMF’s Role in Strengthening Fiscal Transparency in Europe -- 5. Conclusions and Policy Recommendations
Includes bibliographical references (p. 53-55)
Keywords: Corruption; POLITICAL CORRUPTION; TRANSPARENCY; EVALUATION; GOVERNMENT POLICY; SOUTHERN EUROPE; Central and Eastern Europe; IMF